Alternating magnetic field enhances cytotoxicity of Compound C. Issue 11 (6th October 2018) - Akimoto, Taisuke; Umemura, Masanari; Nagasako, Akane; Ohtake, Makoto; Fujita, Takayuki; Yokoyama, Utako; Eguchi, Haruki; Yamamoto, Tetsuya; Ishikawa, Yoshihiro
Abstract: We previously reported the efficacy of anti‐cancer therapy with hyperthermia using an alternating magnetic field (AMF) and a magnetic compound. In the course of the study, unexpectedly, we found that an AMF enhances the cytotoxicity of Compound C, an activated protein kinase (AMPK) inhibitor, although this compound is not magnetic. Therefore, we examined the cellular mechanism of AMF‐induced cytotoxicity of Compound C in cultured human glioblastoma (GB) cells. An AMF (280 kHz, 250 Arms) for 30 minutes significantly enhanced the cytotoxicity of Compound C and promoted apoptosis towards several human GB cell lines in vitro. The AMF also increased Compound C‐induced cell‐cycle arrest of GB cells at the G2 phase and, thus, inhibited cell proliferation. The AMF increased Compound C‐induced reactive oxygen species production. Furthermore, the AMF decreased ERK phosphorylation in the presence of Compound C and suppressed the protective autophagy induced by this compound. The application of an AMF in cancer chemotherapy may be a simple and promising method, which might reduce the doses of drugs used in future cancer treatment and, therefore, the associated side effects. Abstract : The present paper aims to apply an alternating magnetic field (AMF) combined with Compound C, a cell permeable AMPK inhibitor, to a novel glioblastoma (GB) treatment. We believe that this is the first report in which an AMF is applied to treatment of GB in combination with an anti‐tumor agent, Compound C. Our results revealed that AMF further enhanced Compound C‐induced cytotoxicity through de‐phosphorylation of ERK and suppression of autophagy in GB cells.